Gas exchange in umbu tree accessions - Donato, Sérgio Luiz Rodrigues; Arantes, Alessandro de Magalhães; Barros, Beatriz Lima; Deus, Joel da Silva de; DE SOUZA PIRES, EDNEI (Comunicata Scientiae, 2023)
The objective of this work was to evaluate gas exchanges in umbu tree accessions. A 5 × 7 × 2 split-split plot experiment was carried out in a completely randomized design (five accessions – BRS-68, EPAMIG-05, BGU-61, BGU-75, and BGU-50 × seven evaluation dates × two reading times – 8 a.m. and 2 p.m.) with three repetitions. The lower leaf temperatures recorded in BRS-68 and EPAMIG 05 accessions favor higher net photosynthetic rates, water use efficiency and instantaneous carboxylation efficiency compared to BGU 61 accession. Umbu tree regulates transpiration by reducing stomatal conductance under high vapor pressure deficit, although the tree increases transpiration as a defense strategy against heat stress, even with a reduction in stomatal conductance. High temperatures limit instantaneous carboxylation efficiency, photosynthetic rate, and the ratio of photosynthesis to radiation incident on the leaf. Transpiration varies directly with stomatal conductance, while intrinsic water use efficiency varies inversely with internal CO2 concentration.